(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Empowerment in woman’s development is a way of defining, challengingand overcoming barriers in her life through which she increases her ability toshape her life. The active, multi-dimensional processes enable them to realizefull identity and power in all spheres of life. Rural women play a crucial rolein agricultural development and allied fields. However without their totalintellectual and physical participation in these activities, it is not possibleto achieve the goals of rural uplift. In the present study an attempt has been made to analyze the presentstatus of women empowerment in different caste categories. The results showedthat majority of the women had medium or low level of empowerment. Furtherwomen who were illiterate/less educated were less empowered and generallybelong to the scheduled caste category. In overall terms, the researchers wouldargue that the broad based approach is one of the best approaches to guaranteegender equity and to empower rural women, and that this approach should beconsidered in the formulation of rural policies and the creation andimplementation of agricultural and rural development programmes and projects. Science and technology inagriculture is of very noteworthy dimension and will strengthen the women inperforming agriculture. Education is going to play a crucial role to utilizescience and technology in a proficient manner. Hence there is an indispensableneed to focus on women education for their empowerment. Keeping in view thepast and the present status of the women in agriculture and also the growth anddevelopment of science and technology in the field of agriculture, a strategicmodel was designed for empowerment of women through agriculture. The strategyconsists of the two ways of empowerment women in agriculture viz Employment andentrepreneurship.